Weights of the world. (Economist, 2026)
The article examines the growing competition between American and Chinese artificial intelligence developers as open-weight Chinese models rapidly close the gap with leading US systems. It discusses how lower costs, wider accessibility, and efficient designs are driving adoption of Chinese AI models worldwide. It also mentions concerns over government restrictions, security risks, and the future availability of open AI technologies.